2015
DOI: 10.1002/jhm.2354
|View full text |Cite
|
Sign up to set email alerts
|

A multifaceted hospitalist quality improvement intervention: Decreased frequency of common labs

Abstract: PURPOSE:Common labs such as a daily complete blood count or a daily basic metabolic panel represent possible waste and have been targeted by professional societies and the Choosing Wisely campaign for critical evaluation. We undertook a multifaceted quality-improvement (QI) intervention in a large community hospitalist group to decrease unnecessary common labs. METHODS:The QI intervention was composed of academic detailing, audit and feedback, and transparent reporting of the frequency with which common labs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
73
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(76 citation statements)
references
References 30 publications
3
73
0
Order By: Relevance
“…Corson et al 8 used emails to educate hospitalists and ask they reduce the number or routine tests ordered. They tracked the number of tests each hospitalist ordered and provided monthly reports to the group detailing how many tests each hospitalist ordered.…”
Section: Introductionmentioning
confidence: 99%
“…Corson et al 8 used emails to educate hospitalists and ask they reduce the number or routine tests ordered. They tracked the number of tests each hospitalist ordered and provided monthly reports to the group detailing how many tests each hospitalist ordered.…”
Section: Introductionmentioning
confidence: 99%
“…The spectrum of laboratory testing overuse in the hospital setting concerns both, the initial patient evaluation and scheduled checks during the follow‐up . The repetition of untargeted laboratory testing during the hospital stay in clinically stable patients represents an example of low‐value care which potentially can harm patients . Ordering laboratory testing at regular intervals (eg, daily) or on a routine basis, could in fact lead to further unnecessary diagnostic and therapeutic procedures potentially producing stress and side‐effects .…”
Section: Introductionmentioning
confidence: 99%
“…Several interventions have been targeted at the inadequacy of blood testing in hospitals. The most successful were those that implemented multifaceted approaches involving a combination of 3 strategies: education, audit, and feedback on provider ordering practices, and restrictive ordering options in the electronic prescription tools . In the context of the Choosing Wisely Campaign, an initiative launched by the American Board of Internal Medicine aimed to target unnecessary low value investigations and treatment and to promote conversation between patients and providers, several medical societies have recommended against routine laboratory testing in hospitalised patients .…”
Section: Introductionmentioning
confidence: 99%
“…4,5 There are few guidelines that address the appropriateness of blood testing practices in hospitalized patients, and there have been concerns that tests are often over-ordered. 6,7,8,9,10 The objective of this study was to describe the proportion of repeat hemoglobin tests that demonstrated a clinically significant drop of at least 1 g/dL when obtained on the same calendar day.…”
Section: Introductionmentioning
confidence: 99%